Implementasi Metode Langsung dalam Pembelajaran Gending Jejangéran Pada Jangér Sakral Banjar Kedaton Sumerta - I Made Bagus Angga Putra; Ni Nyoman Perni; I Made Wiradnyana (Cetta: Jurnal Ilmu Pendidikan, 2026)
The preservation of the Balinese language and sacred traditional arts requires learning strategies that are not only practice-oriented but also capable of sustaining cultural values. Although the Direct Method has been widely applied in language learning, studies specifically examining its implementation in teaching gending jejangéran within the context of Sacred Jangér as a medium for language and cultural preservation remain limited. This study aims to describe the implementation of the Direct Method in teaching gending jejangéran in Banjar Kedaton, Désa Adat Sumerta, Denpasar City, identify the constraints and solutions that emerge during the learning process, and explain its implications for instructors, dancers, and the community. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings show that the Direct Method was implemented through stages of spiritual and ethical preparation, goal orientation, demonstration, imitation, repetition, immediate correction, and follow-up evaluation. The main constraints included differences in dancers’ comprehension, limited mastery of the Balinese language, difficulties in synchronizing vocal performance with movement and rhythm, and limited practice time. These constraints were addressed through material segmentation, repeated practice, direct feedback, and independent practice. This study highlights that the Direct Method is not only effective as a strategy for teaching traditional vocal arts, but also contributes theoretically by extending its application from language pedagogy to traditional arts pedagogy rooted in local culture, while strengthening the preservation of the Balinese language and Sacred Jangér.